Efektivitas pelatihan resiliensi untuk menurunkan stres akademik mahasiswa: Randomized PreTest, PostTest and Follow-Up: Effectiveness of resilience training to reduce academic stress in college students: Randomized PreTest, PostTest and Follow-Up - Nurlaila, Siti; Hanurawan, Fattah; Eva, Nur; Chusniyah, Tutut (Persona:Jurnal Psikologi Indonesia, 2024)
Academic stress not only occurs in students at school but also occurs in many college students. Several studies have shown that irrational thoughts about self-confidence and low resilience are related to high academic stress. This study aims to analyze the effectiveness of resilience training to reduce academic stress in students. This study is an experimental study with a Randomized Pre-Test, Post-Test, and Follow-Up (RPPF) design. Researchers randomly divided participants into experimental and control groups. The experimental group received eight sessions of resilience training intervention for three weeks, with two to three sessions per week, each lasting 90 minutes. Both groups underwent measurements before the intervention (pre-test), after the intervention (post-test), and two weeks after the intervention (follow-up). This research instrument used an academic stress scale (α =0.842). Data analysis using Multivariate Analysis of Covariance showed that resilience training had significant effectiveness in reducing academic stress in students. The implications of further research are discussed.